Temperate Forest Floor Bryophytes Functionally Respond to Small‐Scale Variability in Water, Light and Nutrient Availability - T. J. Deilmann; M. Bernhardt‐Römermann; J. Hentschel; P. Gros; C. Römermann (Ecology and Evolution)
ABSTRACT Bryophytes form an integral component in numerous ecosystems. They impact ecosystem processes by regulating water, carbon, and nutrient input into the soil, making them an ecologically significant but understudied group of plants. To understand ecosystem processes, functional traits offer a suitable tool as they reflect plant performance and strategies that respond to changes in the environment. Functional traits, however, have been hardly studied and are still poorly understood in bryophytes, limiting the understanding of functional responses to environmental variability and future change. Therefore, we here measured 10 functional traits related to water balance (e.g., leaves per cm, branching density, water uptake capacity) and productivity (e.g., shoot length, in situ fluorescence, specific shoot area) and related them to environmental variability for eight common forest floor bryophyte species in two temperate coniferous forests. We tested how well these traits respond to small‐scale variability in water, light, and nutrient availability. Multivariate analyses showed a large variation in trait composition of the investigated species, mainly driven by growth form (pleurocarpous vs. acrocarpous), while the impact of forest type (Norway spruce vs. Scots pine) on trait composition seemed less important. Mixed effects models across all species revealed that traits were very sensitive to within‐forest small‐scale variability; for example, leaves per cm or in situ fluorescence were positively related to increasing plot‐level characteristics such as leaf area index and throughfall, again with growth form‐specific responses. We further found intraspecific trait variation for the most dominant bryophyte species, indicating considerable phenotypic plasticity. We conclude that moss trait variability is more linked to growth form than to forest type, and that both bryophyte communities and individual species are functionally sensitive to small‐scale environmental variability. We therefore emphasize including bryophytes and growth form as a functional group more specifically in functional response studies.